Curative distal pancreatectomy in patients with acinar cell carcinoma of pancreas diagnosed by endoscopic aspiration via esophago-jejunostomy: A successful case report. (2018) - Hamada, Takeomi; Nanashima, Atsushi; Hiyoshi, Masahide; Ikenoue, Makoto; Imamura, Naoya; Yano, Koichi; Fujii, Yoshiro; Kubota, Yoshimasa; Ban, Tesshin; Kawakami, Hiroshi; Sato, Yuichiro
Highlights: This is a rare report of acinar cell carcinoma of pancreas diagnosed preoperatively. Accurate histological diagnosis was performed by endoscopic FNA via jejunal loop after gastrectomy. Accurate histological diagnosis is useful in the field of pancreatic surgery, especially in cases of rare or small malignant lesions. Abstract: Introduction: This is a case report on the advances in preoperative endoscopic-guided fine-needle-aspiration (FNA) diagnosis for pancreatic carcinoma to achieve a curative operation even in patients who have a history of total gastrectomy. Case presentation: A 65-year-old man, who underwent total gastrectomy for gastric cancer 13 years ago, had discomfort in the left lateral abdomen. A 3-cm hypovascular mass accompanying a large distal pseudocyst in the pancreatic tail was observed on computed tomography. Endoscopic ultrasonography via elevation of the jejunal loop on esophago-jejunostomy also revealed similar lesions, and FNA for the proximal-side hypoechoic mass was successful. The cytological diagnosis with immunohistochemistry was acinar cell carcinoma of the pancreas. Distal pancreatectomy with splenectomy was successfully performed. Histology of the resected specimen also showed the acinar cell carcinoma, similar with preoperative cytology, which involved the splenic vein and had extra-pancreatic extension but no lymph node metastasis. The tumor stage was IIA by the 2009 UICC classification. He had no tumor relapse on imaging follow-up until 12 months after the operation. Discussion: There have been marked technical advancements in endoscopic ultrasonography-guided diagnosis, including FNA, even in patients with prior digestive tract surgery. However, the risk of complication is still a concern. Accurate histological diagnosis is useful in the field of pancreatic surgery, especially in cases of rare or small malignant lesions. Conclusion: Curative pancreatectomy was possible in a case of acinar cell carcinoma, a rare pancreatic malignancy, which was diagnosed by preoperative endoscopic FNA diagnosis via esophago-jejunostomy after previous total gastrectomy.